Every hour until then - Meyer, Gabrielle (Meyer, Gabrielle. Timeless, 2025)
"As a time-crosser, Kathryn Voland lives in 1888 England and pre-World War II Washington, DC. When she curates a museum exhibit about Jack the Ripper, she discovers that her sister will become his last victim in 1888. Kathryn must race time to save her, knowing it will cost her everything--including the only man she's ever loved."--